Maternal and perinatal outcome following assisted reproductive technology in a tertiary care centre: a retrospective study - Valvi, Durga; Swaminathan, Girija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is a major issue and a source of social and psychological suffering for many couples. Introduction of assisted reproductive technology (ART) leads to great relief for couples nowadays. Methods: Present study was a retrospective study conducted at K.E.M hospital, a major tertiary care hospital after approval of the institutional ethics committee. A retrospective analysis of maternal and perinatal outcome of 30 cases of ART conception from the year 2014 to 2018 was done. Results: The mean age of women enrolled into present study was 37.6 years and most common age group was 30-50 years. The main cause of infertility was unexplained (40%), other causes were female factor (33.33%), male factor (16.67%) and combined (10%). 63.33% pregnancies were singleton and 36.67% twin gestations. The most common complication seen was preterm labour (43.33%). The other complications were preeclampsia/eclampsia (33.33%), gestational hypertension, renal failure, gestational diabetes, cardiomyopathy, hepatic failure, HELLP syndrome and DIC. 60% patients had caesarean section and 40% had vaginal delivery.90.24% neonates had 5-minute Apgar score of more than or equal to 7 and 9.76% had score less than 7. There were 4 stillbirths accounting for 9.76% and out of live births,75.68% babies required NICU admission. There were 5 neonatal deaths (12.2%) and perinatal death rate was 21.95%. Conclusions: ART is associated with a variety of maternal and perinatal complications. Couples should therefore be counseled about these risks while offering them ART as a mode of conception.